Estimating refractivity from propagation loss in turbulent media. Issue 12 (15th December 2016) - Wagner, Mark; Gerstoft, Peter; Rogers, Ted
Abstract: This paper estimates lower atmospheric refractivity (M‐profile) given an electromagnetic (EM) propagation loss (PL) measurement. Specifically, height‐independent PL measurements over a range of 10–80 km are used to infer information about the existence and potential parameters of atmospheric ducts in the lowest 1 km of the atmosphere. The main improvement made on previous refractivity estimations is inclusion of range‐dependent fluctuations due to turbulence in the forward propagation model. Using this framework, the maximum likelihood (ML) estimate of atmospheric refractivity has good accuracy, and with prior information about ducting the maximum a priori (MAP) refractivity estimate can be found. Monte Carlo methods are used to estimate the mean and covariance of PL, which are fed into a Gaussian likelihood function for evaluation of estimated refractivity probability. Comparisons were made between inversions performed on propagation loss data simulated by a wide angle parabolic equation (PE) propagation model with added homogeneous and inhomogeneous turbulence. It was found that the turbulence models produce significantly different results, suggesting that accurate modeling of turbulence is key. Key Points: Turbulence acting on EM propagation loss can be modeled by adding fluctuations to a forward propagation loss model at discrete range steps Atmospheric refractivity profile estimation is not as accurate as previously thought when considering randomness introduced by turbulence A genetic algorithm can be used to invert for a height‐varying refractivity profile given propagation loss measurements over range